2007
DOI: 10.1039/b608411g
|View full text |Cite
|
Sign up to set email alerts
|

A computational study on N2adsorption in Cu-ZSM-5

Abstract: The present computational study investigates the adsorption of N(2) by Cu-ZSM-5, with particular regard to the interaction with pairs of Cu(+) ions, employing simple cluster models in the calculations. It shows that several interaction patterns between N(2) and couples of Cu(+) sites are possible within the Cu-ZSM-5 structure. In particular, when pairs of Cu(+) ions are located at opposite sides of ten-membered rings, in the region where linear and sinusoidal channels intersect each other, a quasi-linear Cu-N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
(131 reference statements)
1
14
0
Order By: Relevance
“…Evidence for Cu 2 2+ dimers has been obtained in previous experimental and theoretical studies, especially for Cu-ZSM-5, where they are believed to play an important role in nitric oxide decomposition: here, previous DFT investigations predicted similarly short Cu + -Cu + distances of about 2.5 Å for some cases. 56,57 The detailed computational study of Cu-chabazite by Go ¨ltl et al also revealed a preference of Cu + (and Cu 2+ , in line with experimental results 58,59 ) for the SII site. 60 However, the aspect of dimer formation was not investigated in that work, which considered a smaller number of cations per cell.…”
Section: Pccp Papersupporting
confidence: 64%
“…Evidence for Cu 2 2+ dimers has been obtained in previous experimental and theoretical studies, especially for Cu-ZSM-5, where they are believed to play an important role in nitric oxide decomposition: here, previous DFT investigations predicted similarly short Cu + -Cu + distances of about 2.5 Å for some cases. 56,57 The detailed computational study of Cu-chabazite by Go ¨ltl et al also revealed a preference of Cu + (and Cu 2+ , in line with experimental results 58,59 ) for the SII site. 60 However, the aspect of dimer formation was not investigated in that work, which considered a smaller number of cations per cell.…”
Section: Pccp Papersupporting
confidence: 64%
“…It is remarkable that ongoing research carried out by several research groups (see, for instance, [ 68 , 69 , 70 , 71 ]) has shown that several copper-exchange zeolites can convert methane into methanol at a relatively mild temperature (150–200 °C), and there is evidence that in Cu-ZSM-5, the catalytic center involves a μ-oxo dicopper complex [ 72 , 73 ]; however, the mechanistic details are yet to be elucidated. Finally, we wish to mention earlier work by several authors [ 74 , 75 , 76 ] showing that Cu-ZSM-5 adsorbs dinitrogen-forming bridged Cu + ···N-N···Cu + complexes on dual Cu + sites. Moreover, the same dual sites were found to be catalytically active in the decomposition of nitrogen oxides.…”
Section: Discussionmentioning
confidence: 95%
“…The observed yields in association with the configuration of the corresponding pentoses clearly indicate a correlation with the existence of acyclic structures of the pentoses during the course of the reaction [68,69]. To overcome the problem of low yields of Knoevenagel addition products we tested 2-hydroxypyridine as an additional catalyst, which is known to have a large effect on the anomerization equilibration of carbohydrates by formation of hydrogen bonds [70][71][72][73][74][75][76][77][78]. By increasing the equilibrium constant, a higher amount of active acyclic form is available per defined time-unit.…”
mentioning
confidence: 93%